Fusion of Unerupted Mesiodens with a Regular Maxillary Central Incisor: a Diagnostic and Therapeutic Challenge - Zdenko Šarac; Ružica Zovko; Stipo Cvitanović; Kristina Goršeta; Domagoj Glavina (University of Zagreb. School of Dental Medicine, 2021)
The mesiodens is the most frequent type of supernumerary tooth which can appear in the maxillary midline area. The etiology of mesiodentes is not fully understood. This report shows a case of incomplete fusion of an unerupted mesiodens with a permanent maxillary central incisor, aligned in the dental arch. Intraoral and radiographic examinations indicated fusion of the crown and cervical part of the root of the supernumerary tooth with the permanent incisor. The clinical situation was further complicated by the presence of another supernumerary tooth located palatally. The treatment approach has included two phase surgical therapy to extract the supernumerary teeth. Early diagnosis and appropriate surgical treatment of mesiodentes are important to decrease the risk of clinical complications. Preoperative 3D imaging is strongly advisable since it allows accurate data to be obtained, and reduces the extent of surgery and the possibility of procedural complications. In most cases, a multidisciplinary collaboration is necessary for precise diagnosis and predictable treatment outcome.